E6/E7 and E6* From HPV16 and HPV18 Upregulate IL-6 Expression Independently of p53 in Keratinocytes - Artaza-Irigaray, Cristina; Molina-Pineda, Andrea; Aguilar-Lemarroy, Adriana; Ortiz-Lazareno, Pablo; Limón-Toledo, Laura P.; Pereira-Suárez, Ana L.; Rojo-Contreras, Wendoline; Jave-Suárez, Luis F. (Frontiers in Immunology, 2019)
Keratinocyte infection with high-risk human papillomavirus genotypes has been linked to cancer development. In cervix, the alpha HPV16 and HPV18 have been reported as the mayor causative agents of cervical cancer. Oncogenic progression and chronic inflammation are closely related processes, with IL-6 as one of the main pro-inflammatory cytokines involved. However, there are limited studies about the regulation of IL-6 by low and high risk HPVs and the HPV proteins implicated in this modulation. In this work, we report the overexpression of IL-6 in HPV infected cervical cancer derived cell lines (HeLa and SiHa) compared to non-tumorigenic keratinocytes (HaCaT), and in Cervical Intraepithelial Neoplasia grade 1 HPV16 and HPV18 positive cervical samples compared to HPV negative samples without lesions. Moreover, we generated HaCaT keratinocytes that express E5, E6 and E7 from high risk (16 or 18) or low risk (62 and 84) HPVs. E5 proteins do not modify IL-6 expression, while E7 modestly increase it. Interestingly, E6 proteins in HaCaT cells upregulate IL-6 mRNA expression and protein secretion. Indeed, in HaCaT cells that express high risk HPV16E6 or HPV18E6 proteins, only the truncated E6* isoforms were expressed, showing the stronger IL-6 overexpression, while in HaCaT cells that express low risk HPV62 and HPV84 full length E6 proteins, IL-6 was also upregulated but not so drastically. Since HaCaT cells have a mutated p53 form that is not degraded by the introduction of E6 or E6/E7, it seems that E6/E7 regulate IL-6 by an additional mechanism independent of p53. In addition, basal keratinocytes showed a strong expression of IL-6R using immunohistochemistry, suggesting an autocrine mechanism over proliferative cells. Altogether, IL-6 cytokine expression in keratinocytes is upregulated by E6 and E7 proteins from HPVs 16, 18, 62 and 84, especially by high risk HPV16 and HPV18 E6*, which may contribute to promote a pro-inflammatory and highly proliferative microenvironment that can persist over time and lead to cervical tumorigenesis.